Knowledge mapping and research trends of IL-22 from 2014 to 2023: A bibliometric analysis - Shu-Zhen Liu; Jie-Hong Xie; Bing-Ju Yan; Jun Wang (Human Vaccines & Immunotherapeutics)
Although IL-22 has been extensively studied, a comprehensive and systematic bibliometric analysis has not yet been conducted on it. This article reviews the research progress of IL-22 using bibliometric methods. On May 20, 2024, publications related to IL-22 were identified and selected from the Web of Science Core Collection (WoSCC) database. CiteSpace and VOSviewer are beneficial for IL-22 bibliometric and knowledge graph analysis. From January 1, 2014 to December 31, 2023, 25134 authors from 4206 institutions in 106 countries published 3943 articles on IL-22 research in 940 academic journals. During this period, the number of articles steadily increased. The United States and China are the main contributors to this research field, with the most active institutions being the Medical Research Institute (INSERM) led by De la Sante et al. and the University of California system. The most prolific journal is Frontiers of Immunology, and it is also the journal with the most citations. Guttman Yassky, E. has published the most articles, and Guttman Yassky, E. is also the most frequently cited. The main areas of these publications are immunology and cell biology. After analysis, the high-frequency keywords of IL-22 research involve molecular biology (IL-17) and immune response (T cells) Th17 cells and diseases (autoimmune diseases, cancer). Among them, the involvement of interleukin-22 in microbial populations and cancer cell spread has strong research potential and is currently a hot research topic. Since 2014, IL-22 has received significant attention in scientific research as a key immune regulatory factor. China is at the forefront of research in this field, followed closely by the United States. At present, breakthrough progress is being made in the research of immunotherapy, and in-depth study of IL-22 and its signal transduction mechanisms is crucial for understanding its biological functions. Meanwhile, exploring new possibilities for IL-22 as a therapeutic target will help develop more effective treatment strategies. This study can provide scholars with research directions related to IL-22.